Investigation of the hydrodynamic processes of a centrifugal pump in a geothermal system - Bogdevičius, Marijonas; Janutėnienė, Jolanta; Didžiokas, Rimantas; Razmas, Saulius; Skrickij, Viktor; Bogdevičius, Paulius (Transport, 2018)
The hydrodynamic and thermodynamic processes of geothermal well extraction are investigated and presented in this paper. The paper presents mathematical models for a multi-level centrifugal pump and pipeline system. The mathematical models were used to evaluate gas (nitrogen) emission in water and its effects on hydrodynamic processes. Experimental studies and mathematical modelling showed that the gas content of the fluid increases the pressure and flow pulsations within a centrifugal pump. The variation in the height of the liquid column in extraction has an influence on characteristics of the multistage centrifugal pump used in wells. First published online 29 March 2016